2020
DOI: 10.1063/5.0009666
|View full text |Cite
|
Sign up to set email alerts
|

Graphene mediated resistive switching and thermoelectric behavior in lanthanum cobaltate

Abstract: Multifunctional materials are of utmost importance owing to the combination of several functionalities into a single device. We present the multifunctional properties, namely, thermoelectric (TE) for energy harvesting and resistive switching (RS) for memory storage in the LaCoO3 (LCO)–graphene nanocomposite system. The existence of individual phases of LCO and graphene is confirmed from x-ray diffraction and electron microscopy techniques. The x-ray photoelectron spectroscopy measurement reveals the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Moreover, the preparation of composite materials is promising for simultaneous optimization of electrical and thermal transport properties to obtain an improved TE performance. This approach allows the utilization of a few transport phenomena that can result in improvement of the σ/κ ratio. The simultaneous filtering of the charge carrier and enhanced phonon scattering at the interface between the Bi 0.4 Sb 1.6 Te 3 -Cu 2 Se nanocomposite results in an enhanced zT (∼1.6 at 488 K) . Kim et al reported an improved zT (∼1.85) in the PbTe-PbSe composite because of the synergistic effect of reduced κ ph and enhanced α 2 σ .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the preparation of composite materials is promising for simultaneous optimization of electrical and thermal transport properties to obtain an improved TE performance. This approach allows the utilization of a few transport phenomena that can result in improvement of the σ/κ ratio. The simultaneous filtering of the charge carrier and enhanced phonon scattering at the interface between the Bi 0.4 Sb 1.6 Te 3 -Cu 2 Se nanocomposite results in an enhanced zT (∼1.6 at 488 K) . Kim et al reported an improved zT (∼1.85) in the PbTe-PbSe composite because of the synergistic effect of reduced κ ph and enhanced α 2 σ .…”
Section: Introductionmentioning
confidence: 99%
“…TE characteristics of pristine and graphene-reinforced nanocomposites, (a) Seebeck coefficients, (b) electrical conductivities, (c) lattice thermal conductivity (E and H show the total thermal conductivity), and (d) dimensionless figure of merit ( zT ): (A) Bi 0.85 Sb 0.15 -0.5 wt %G ( T = 280 K), (B) Nb-doped SrTiO 3 -RGO ( T = 800 K), (C) Zn 0.98 Al 0.02 O-1.5 wt %RGO ( T = 900 °C), (D) p -phenediamino-modified graphene (PDG) (RT), (E) CoSb 3 /G ( T = 800 K), (F) LaCoO 3 -0.01 wt % G ( T = 300 K), (G) MnTe-GNPs ( T = 823 K), (H) CuInTe 2 /G (80:1) mass ratio ( T = 700 K), (I) SnSe-3.2 wt % MoS 2 /G ( T = 810 K) …”
Section: Introductionmentioning
confidence: 99%
“…The effect of graphene segregation at the grain interfaces can be evaluated, based on the possible band alignment, depending on the work functions of graphene and the main matrix. As illustrated in Figure 3, the type of contact (Schottky or 16 (C) Zn 0.98 Al 0.02 O-1.5 wt %RGO (T = 900 °C), 17 (D) p-phenediaminomodified graphene (PDG) (RT), 18 (E) CoSb 3 /G (T = 800 K), 19 (F) LaCoO 3 -0.01 wt % G (T = 300 K), 20 (G) MnTe-GNPs (T = 823 K), 21 (H) CuInTe 2 /G (80:1) mass ratio (T = 700 K), 22 (I) SnSe-3.2 wt % MoS 2 /G (T = 810 K). Therefore, these extra boundaries due to smaller grain sizescaused by graphene segregation and grain growth blockingand graphene-matrix interfaces may provide an energy filtering effect for the charge carriers (electrons or holes).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the available reports in literature, the composite TE materials is an effective strategy to improve the zT via reduction of 𝑘 ph in several systems including SrTiO 3 -graphene [12], LaCoO 3 -graphene [13], CoSb 3 -WO 3 [14], Na 0.77 CoO 2 -Ca 3 Co 4 O 9 [15], (Ca 0.9 Ag 0.1 ) 3 Co 4 O 9 -Ag [16], Ca 3 Co 4 O 9 -La 0.8 Sr 0.2 CoO 3 [17] and also in several other composite systems [18] [19]. However, the studies in the literature on the TE composite materials focus on the improvement of transport properties and rarely consider the effect of 𝑅 𝑖𝑛𝑡 between the phases.…”
Section: Introductionmentioning
confidence: 99%